Tugas dan Tanggung Jawab Dinas Pendidikan Menuju Tertib Administrasi Pendidikan Yang Efisien dan Produktif - Susanto, Hasperi (Yayasan Sembilan Pemuda Indonesia, 2022)
The education office has been present in Indonesia since independence was proclaimed. In its development the work program of the service always experiences amazingly fast dynamics. This is in order to meet the needs of the educational academic community in the field. This study aims to describe the duties and responsibilities of the Department of Education in carrying out its program so that it can be useful for the community. The research method used in this research is literature study. The main data in this research is based on published journal articles which are corroborated by arguments about theories in education management. The findings in this study are the education office implements its work program in the duties and main functions of the education office. It has the same meaning as a work program.